2016
DOI: 10.1038/srep37991
|View full text |Cite
|
Sign up to set email alerts
|

Principal function of mineralocorticoid signaling suggested by constitutive knockout of the mineralocorticoid receptor in medaka fish

Abstract: As in osmoregulation, mineralocorticoid signaling is implicated in the control of brain-behavior actions. Nevertheless, the understanding of this role is limited, partly due to the mortality of mineralocorticoid receptor (MR)-knockout (KO) mice due to impaired Na+ reabsorption. In teleost fish, a distinct mineralocorticoid system has only been identified recently. Here, we generated a constitutive MR-KO medaka as the first adult-viable MR-KO animal, since MR expression is modest in osmoregulatory organs but hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 62 publications
2
41
0
Order By: Relevance
“…Previous reports using knockout fish models indicate that MR plays an important role in regulating HPI axis function (Faught & Vijayan, ) and stress‐related behaviour (Sakamoto et al . ; Faught & Vijayan, ). In combination with mammalian work (Joëls & de Kloet, ), this suggested that the primary role for this receptor may have been in stress sensing and appraisal prior to its mineralocorticoid role in the tetrapod lineage (Baker et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports using knockout fish models indicate that MR plays an important role in regulating HPI axis function (Faught & Vijayan, ) and stress‐related behaviour (Sakamoto et al . ; Faught & Vijayan, ). In combination with mammalian work (Joëls & de Kloet, ), this suggested that the primary role for this receptor may have been in stress sensing and appraisal prior to its mineralocorticoid role in the tetrapod lineage (Baker et al .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of Aldo in fish has led to speculation that F and DOC may be a physiological mineralocorticoid for fish (Baker 2003, Sturm et al 2005, Prunet et al 2006, Baker et al 2007, Bury & Sturm 2007, McCormick et al 2008, Arterbery et al 2011, Sakamoto et al 2011, Takahashi & Sakamoto 2013, Sakamoto et al 2016. Interestingly, Prog is a transcriptional activator of ray-finned fish, which also respond to 19-norProg and spironolactone (Sturm et al 2005, Pippal et al 2011, Sugimoto et al 2016).…”
Section: Transcriptional Activation Of Fish Mr By Prog a Possible MImentioning
confidence: 99%
“…Thus, during the evolution of the MR in cartilaginous fishes, ray-finned fishes and terrestrial vertebrates, there have been changes in the EC50 of the MR for 3-ketosteroids (Sturm et al 2005, Carroll et al 2008, Pippal et al 2011, Sugimoto et al 2016, as well as the MR's physiological function (Vize & Smith 2004, Hawkins et al 2012, Martinerie et al 2013, Rossier et al 2015, Jaisser & Farman 2016, Mifsud & Reul 2016, Sakamoto et al 2016. It needs to be noted that transcriptional activation by corticosteroids of fish MRs is studied in mammalian cells, which may provide different responses than in assays using homologous fish cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, during the evolution of the MR in cartilaginous fishes, ray-finned fishes and terrestrial vertebrates, there have been changes in MR specificity for corticosteroids, as well as the MR's physiological function (Hawkins et al 2012;Jaisser and Farman 2016;Martinerie, et al 2013;Mifsud and Reul 2016;Rossier et al 2015;Sakamoto, et al 2016;Vize and Smith 2004).…”
Section: Figure 3 Pathway For Synthesis Of Aldosterone From Progestermentioning
confidence: 99%
“…The absence of Aldo in fish has led to speculation that F and DOC may be a physiological mineralocorticoid for fish (Arterbery et al 2011;Baker 2003;Baker et al 2007;Bury and Sturm 2007;McCormick, et al 2008;Prunet et al 2006;Sakamoto et al 2011;Sakamoto et al 2016;Sturm et al 2005;Takahashi and Sakamoto 2013). Interestingly Prog is a transcriptional activator of ray-finned fish, which also respond to 19-norProg and spironolactone (Pippal et al 2011;Sturm et al 2005;Sugimoto et al 2016 (Chapman et al 2013;Odermatt and Kratschmar 2012).…”
Section: Transcriptional Activation Of Fish Mr By Prog a Possible MImentioning
confidence: 99%